Medios de Comunicación de Iberoamérica en la Web (Caso México) - Guamán Hurtado, Diana Lisseth (2018)
Abstract:Iberoamerican Media on the Web (Mexican case), is a study that aims to know the development and introduction of cyber journalism in Mexico, to obtain consumer trends and web design, that allow generating comparisons at the Iberoamerican level. For the case of Mexico, the sample consisted of 8 digital media (from television, press and digital natives), chosen for being the best positioned in the ranking of the Alexa platform. In addition, these media were subjected to a mixed analysis through the application of a technical file, the results were an updated information about the use that Mexican cybermedia is giving to Web 2.0 tools such as: accessibility, new trends of journalism, interaction tools, usability, media morphology, constant updating, hypertextuality and multimedia. Apart from identifying new challenges in the Mexican context, caused by the increase of social networks as a means of information, mobile phones as the main digital support, tools for citizen participation, among others.